Clinical characteristics and outcomes of acute kidney injury in patients with severe fever with thrombocytopenia syndrome - Zhang, Zhongwei; Hu, Xue; Jiang, Qunqun; Hu, Wenjia; Li, Anling; Deng, Liping; Xiong, Yong (Frontiers in Microbiology, 2023)
Background Severe fever with thrombocytopenia syndrome (SFTS) is an emerging zoonosis caused by a novel bunyavirus. Until recently, the SFTS related acute kidney injury (AKI) was largely unexplored. This study aimed to investigate the clinical characteristics and outcomes of AKI in patients with SFTS. Methods The non-AKI and AKI groups were compared in terms of general characteristics, clinical features, laboratory parameters and cumulative survival rate. The independent risk factors for in-hospital mortality in patients with SFTS were analyzed by multivariate logistic regression to identify the population with poor prognosis. Results A total of 208 consecutive patients diagnosed with SFTS were enrolled, including 153 (73.6%) patients in the non-AKI group and 55 (26.4%) patients in the AKI group. Compared with patients without AKI, patients with AKI were older and had a higher frequency of diabetes. Among these laboratory parameters, platelet count, albumin and fibrinogen levels of patients with AKI were identified to be significantly lower than those of patients without AKI, while ALT, AST, ALP, triglyceride, LDH, BUN, uric acid, creatine, Cys-C, β2-MG, potassium, AMY, lipase, CK-MB, TnI, BNP, APTT, thrombin time, D-dimer, CRP, IL-6, PCT and ESR levels were significantly higher in patients with AKI. A higher SFTS viral load was also detected in the AKI patients than in the non-AKI patients. The cumulative survival rates of patients at AKI stage 2 or 3 were significantly lower than those of patients without AKI or at AKI stage 1. However, there was no significant difference in the cumulative survival rates between patients without AKI and those with stage 1 AKI. Univariate and multivariate binary logistic regression analyses demonstrated that stage 2 or 3 AKI was an independent risk factor for in-hospital mortality in patients with SFTS. Conclusion AKI is associated with poor outcomes in patients with SFTS, especially patients at AKI stage 2 or 3, who generally have high mortality. Our findings support the importance of early identification and timely treatment of AKI in patients with SFTS.